2020
DOI: 10.1111/jfpe.13358
|View full text |Cite
|
Sign up to set email alerts
|

Use of artificial intelligence for the estimation of effective moisture diffusivity, specific energy consumption, color and shrinkage in quince drying

Abstract: In the study, drying process of quince fruit was accomplished in a microwave‐convective dryer (MCD). The experiments were carried out at microwave power levels of 100, 200, and 300 W, air temperatures of 40, 55, and 70°C, and air velocities of 0.5, 1, and 1.5 m/s. Nevertheless, three artificial intelligence techniques consisted of artificial neural networks (ANNs), particle swarm optimizer (PSO), and grey wolf optimizer (GWO) were evaluated to predict the parameters of Deff, SEC, ΔE, and Sb. In the evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 66 publications
10
38
0
Order By: Relevance
“…The activation energy of control samples ranging from 23.59 to 25.83 kJ/mol with an average value of 24.81 kJ/mol for the forced convection drying, 25.83 to 31.72 kJ/mol with an average of 28.19 kJ/mol for natural convection drying and 29.51 to 38.95529 kJ/mol with an average of 33.34 kJ/mol for open sun drying process. The effective moisture diffusivity of the dried ivy gourd sample of the current investigation results were in good agreement and comparable with the other literature review of food products, Kaveh, Jahanbakhshi, Abbaspour‐Gilandeh, Taghinezhad, and Moghimi (2018), Abbaspour‐Gilandeh, Kaveh, and Jahanbakhshi (2019), Ojediran et al (2020) and Taghinezhad, Kaveh, Jahanbakhshi, and Golpour (2020). With respect to the activation energy of ivy gourd, the present investigation results were also in good agreement and comparable with the existing literature review of food substances, Kaveh et al (2018) and Ojediran et al (2020).…”
Section: Resultssupporting
confidence: 91%
“…The activation energy of control samples ranging from 23.59 to 25.83 kJ/mol with an average value of 24.81 kJ/mol for the forced convection drying, 25.83 to 31.72 kJ/mol with an average of 28.19 kJ/mol for natural convection drying and 29.51 to 38.95529 kJ/mol with an average of 33.34 kJ/mol for open sun drying process. The effective moisture diffusivity of the dried ivy gourd sample of the current investigation results were in good agreement and comparable with the other literature review of food products, Kaveh, Jahanbakhshi, Abbaspour‐Gilandeh, Taghinezhad, and Moghimi (2018), Abbaspour‐Gilandeh, Kaveh, and Jahanbakhshi (2019), Ojediran et al (2020) and Taghinezhad, Kaveh, Jahanbakhshi, and Golpour (2020). With respect to the activation energy of ivy gourd, the present investigation results were also in good agreement and comparable with the existing literature review of food substances, Kaveh et al (2018) and Ojediran et al (2020).…”
Section: Resultssupporting
confidence: 91%
“…Ultrasonic pretreatment prevents the formation of this layer, hence increasing the moisture removal rate, shortening the drying time, and hence reducing the SEC value [ 20 ]. Similar results were reported for drying parsley leaves by a microwave-convective dryer [ 11 ] and blackberry by an HCIR dryer [ 43 ]; as they showed that ultrasound pretreatment can result in lower SEC values, compared to the blanching pretreatment.…”
Section: Resultssupporting
confidence: 84%
“…It has a large effect on the product quality. By reducing the moisture content to a certain level in fruits and vegetables, the microbiological decay and deteriorative chemical reactions are remarkably minimized (Taghinezhad et al, 2020).…”
Section: Introductionmentioning
confidence: 99%